2015
DOI: 10.1021/acsami.5b09579
|View full text |Cite
|
Sign up to set email alerts
|

Pt- and TCO-Free Flexible Cathode for DSSC from Highly Conducting and Flexible PEDOT Paper Prepared via in Situ Interfacial Polymerization

Abstract: Here, we report the preparation of a flexible, free-standing, Pt- and TCO-free counter electrode in dye-sensitized solar cell (DSSC)-derived from polyethylenedioxythiophene (PEDOT)-impregnated cellulose paper. The synthetic strategy of making the thin flexible PEDOT paper is simple and scalable, which can be achieved via in situ polymerization all through a roll coating technique. The very low sheet resistance (4 Ω/□) obtained from a film of 40 μm thick PEDOT paper (PEDOT-p-5) is found to be superior to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…The FSG based q‐DSSC shows low FF due to poor charge transfer of tri‐iodide species at electrode/electrolyte interface.This was clearly observed in LSV of FSG dummy cells (Figure S8, Supporting Information) that implies the absence of faradaic or non‐faradaic reaction even at higher potential. After the growth of CPs on FSG surface, an efficient reduction of tri‐iodide species was observed and hence the enhancement in PCE.However, the open circuit voltage (V oc ) of FSG/CPs is less compared to Pt/FTO asit is similar to reported literature based on CPs CEs. To understand the CE/electrolyte interface, EIS characterization was examined under illumination conditions and its interface studies was observed at high frequency region and photoanode‐electrolyte interface at low frequency region.…”
Section: Photovoltaic Behaviour Of Fsg/cpsmentioning
confidence: 99%
“…The FSG based q‐DSSC shows low FF due to poor charge transfer of tri‐iodide species at electrode/electrolyte interface.This was clearly observed in LSV of FSG dummy cells (Figure S8, Supporting Information) that implies the absence of faradaic or non‐faradaic reaction even at higher potential. After the growth of CPs on FSG surface, an efficient reduction of tri‐iodide species was observed and hence the enhancement in PCE.However, the open circuit voltage (V oc ) of FSG/CPs is less compared to Pt/FTO asit is similar to reported literature based on CPs CEs. To understand the CE/electrolyte interface, EIS characterization was examined under illumination conditions and its interface studies was observed at high frequency region and photoanode‐electrolyte interface at low frequency region.…”
Section: Photovoltaic Behaviour Of Fsg/cpsmentioning
confidence: 99%
“…Although the overall thickness of the device was only 0.17 mm, a power density of 1 mW h cm −3 was delivered (Figure c). Moreover, such flexible PEDOT paper can be extended to other electronic devices, such as solar cells, LEDs, and other devices,[22a,145] owing to its simple and scalable synthetic approach.…”
Section: Approaches To Boost Functionsmentioning
confidence: 99%
“…GD:PEDOT:PSS paper electrodes also presented lower resistance and higher flexibility compared to Pt coated cellulose. [100] Anothumakkool et al [117] reported a PEDOT:PSS electrode deposited using immersion technique. The high conductivity of the electrode (Rs = 4 Ω/□) was attributed to the multi-layer structure of PEDOT.…”
Section: Opaque Electrodesmentioning
confidence: 99%